2014
DOI: 10.1007/s00167-014-3007-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gastrocnemius tensiomyographic neuromuscular characteristics as risk factors for anterior cruciate ligament injury in male soccer players

Abstract: Neuromuscular characteristics in terms of mechanical and contractile properties of the gastrocnemius muscles may not be significant risk factors for ACL injury in male soccer players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…However, none of them have compared the TMG values between the dominant and non-dominant lower extremity. In contrast, they have employed the TMG to assess risk factors for anterior cruciate ligament injuries [1,2] and to assess the effects of cold water exposure [10], recovery interventions (after training sessions) [22], playing position [21], anterior cruciate ligament reconstruction [3], and different types of training [24] on mechanical and contractile properties of skeletal muscles of the lower extremity. Most of these studies have employed the dominant side only to conduct their investigation [10,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of them have compared the TMG values between the dominant and non-dominant lower extremity. In contrast, they have employed the TMG to assess risk factors for anterior cruciate ligament injuries [1,2] and to assess the effects of cold water exposure [10], recovery interventions (after training sessions) [22], playing position [21], anterior cruciate ligament reconstruction [3], and different types of training [24] on mechanical and contractile properties of skeletal muscles of the lower extremity. Most of these studies have employed the dominant side only to conduct their investigation [10,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The rest of the parameters obtained with TMG depend on D m : the delay time (T d ), also known as reaction or activation time, is the time between the initiation and 10 % of D m ; the contraction time (T c ) is the time between 10 and 90 % of D m ; the sustained time (T s ) is the time in which the muscle response remains >50 % of D m ; and the half-relaxation time (T r ) is the time in which the muscle response decreases from 90 to 50 % of D m . The measurement methods and protocol were established according to Rey et al [21] and have been previously detailed [1][2][3]. All measurements were obtained at rest in the supine position for the VM, VL, and RF, and in the prone position for the rest of muscle groups.…”
Section: Methodsmentioning
confidence: 99%
“…Soccer studies focussing on injury have described how reconstructive surgery and subsequent rehabilitation, following anterior cruciate ligament injury, have resulted in modified contractile mechanics of muscles in lower extremities on the injured limb, compared with both the contralateral limb and to uninjured soccer players [ 74 ]. Furthermore, Alentorn-Geli et al [ 75 , 76 ] have proposed TMG as an appropriate screening tool to investigate knee flexor muscle stiffness as a risk factor for anterior cruciate ligament injury, with injured individuals presenting greater Dm and longer Tc (in the uninjured limb) compared with injury-free individuals [ 75 ]. The authors suggested that these differences, between individuals who have experienced an anterior cruciate ligament injury and those with no history of an anterior cruciate ligament injury, could hint at elevated susceptibility to ligament injury.…”
Section: Applications Of Tensiomyographymentioning
confidence: 99%
“…Monitoring of asymmetry has also been conducted to assess the effectiveness of rehabilitation programmes and to inform when an individual is able to return to their sport or activity [ 106 ]. Tensiomyography allows for assessment of asymmetry at the individual muscle level, allowing the specific muscle underlying any bilateral imbalance to be identified [ 74 76 ]. Asymmetric TMG responses have been reported in injured soccer players, prior to anterior cruciate ligament reconstruction, with greater symmetry restored following surgery [ 74 ].…”
Section: Applications Of Tensiomyographymentioning
confidence: 99%
“…Furthermore, despite significant improvement in the ATs of hamstring and quadricep muscles after ACLR, they were still slower than those of controls. Therefore, the faster AT of the triceps surae after ACLR may represent a compensatory mechanism to increase joint stability [ 43 , 44 , 45 ] for the weakness and delayed muscle reaction times of hamstring and quadricep muscles. In addition, these faster ATs may partly explain the agonist role of both gastrocnemius and soleus muscles for the ACL.…”
Section: Discussionmentioning
confidence: 99%